Assessment of Electoral Management and Democratization System in Nigeria: A Case of Independent National Electoral Commission (INEC) - Ugoh, Samuel C.; Ukpere, Wilfred I. (Journal of Reviews on Global Economics, 2019)
Nigeria is a country in transition. Since election constitutes a vital ingredient of every participatory democracy, the electoral system therefore is very vital in a country still under transition. Democracy, often, is based on its interface with development. Thus, if democracy is practiced in a manner that accommodates majority of the populace, it has the capacity to jump start human development. In Nigeria, however, the system of democracy has been intercepted by illegitimate regimes over the years, and thereby undermining national development. The relationship between the democracy and development engendered debates over the years among scholars and policy makers. This paper therefore postulates that the electoral institution in Nigeria could be blamed for ushering illegitimate governments, owning to their failure to conduct free and fair elections. The paper concludes that a policy should be formulated to strengthen the electoral body, Independent National Electoral Commission (INEC) to make it truly independent in carrying out the mandate of the people.